Bone metastasis as the first symptom of tumors: role of an immunohistochemistry study in establishing primary tumor - Kim,Leandro Duil (2018)
ABSTRACT Objectives: To determine the role of immunohistochemistry in identifying the primary site of tumors, and in establishing which bones are most frequently involved, their relationship with the primary tumor site, and the rate of pathologic bone fracture as the first symptom of a malignant tumor. Methods: A retrospective analysis of all medical records on bone metastases the cases treated between January 2006 and December 2011 at the Department of Orthopedics and Traumatology was performed. Results: Immunohistochemistry correctly determined the primary tumor site in 61.2% of cases analyzed. Regarding the metastatic site, the most affected bone was the femur, accounting for 49.6% of the sample. Bone metastasis was the first symptom of the tumor in only 20.2% of patients, and of these, 95% were admitted for pathologic bone fracture. Conclusion: The study showed that the primary sites and their incidence rate are consistent with the literature reviewed. It was noted that in this sample, most patients did not present with pathologic bone fracture as the first clinical symptom of neoplastic disease. However, analysis of those patients that had a metastasis as the first clinical symptom revealed that it manifested itself as a pathologic fracture in almost all cases. The immunohistochemical study was consistent with the primary tumor site in most cases, indicating the value of the method in the detection of the primary site.